Marketing on the Move: From Traditional to Greener Making Coherent for the Friendly Environment - Shrivastava, Ajit; Rai , Shivam (Gyan Management Journal, 2018)
The purpose of this paper is to determine the development of the definition of green marketing,  problems, the role of marketers and consumer behaviour towards green marketing. This paper  provides a conceptual method of green marketing by conducting a literature study of research on green  marching. The result can be concluded that marketers have two roles, namely as creators of behaviour  change by providing green products and education. And the second marketer as a search for factors  that influence consumers in buying green products. This is done by marketers because the market has  not been created and marketers still do not understand the black box of consumers towards. This  minimization is possibly the most essential social responsibility of the enterprises. In order to fulfil this,  they ought to undertake environmental pleasant policies in the manufacturing administration and  consist of environmental problems in their manufacturing functions. Newly, environmental sensitivity  has been growing quickly. Business uses clean production technological know-how as for proving  whose environmental sensitivity and responding their client demands. For this reason, market  research, enchantment of marketing strategies has to be accomplished and the shoppers are  knowledgeable and satisfied about the surroundings protective products. Green marketing is an  activity designed to generate and facilitate various changes to obtain satisfaction from what is desired  and needed by humans, by minimizing the effects that damage the environment. Green marketing is  very important because of the limited availability of natural resources. One product that consumers  constantly use is electricity. Most consumers are willing to pay more to get environmentally friendly  renewable energy. This is evidenced by a study in the United States about increasing customer demand  for renewable energy. Both green marketing and products made from environment-friendly materials  are well recommended by experts who believe that such exercise controls the pandemic impact on  nature.
Keywords: Marketing; Green Marketing; Green Products; Consumer Behavior; Environment Sensitivity